PROBLEM - BASED LEARNING IN BASIC PHYSICS - I - Mody, A.K.; Pradhan, H.C. (SCHOOL SCIENCE, 2011)
In this article— first in the series of articles, we present a problem-based learning course that we have used successfully to build capacity of physics students. We present the learning objectives in different areas of basic physics and what each problem tries to achieve with its solution.